Lost in Lost : Entre quotidien anodin et déstabilisation fantastique, entre réalité alternative et fiction collective - Sarah Hatchuel (TV Series, 2012)
This text will be an extension of the reflections on the narrative procedures of Lost, which blur the limits between the “real” and fantasy. In this case, we will analyze the narrative structure of season 6 through the original procedure of the “flash-sideways” (or “flash-ahead”). The “flash-sideways” of Lost challenge the viewer’s comprehension, mixing up narrative and temporal markers and prompting the construction of a true theory of narrative. The “flash-sideways” oscillates between the construction of an alternative temporal reality (which functions like a reflexive palimpsest—the series rewriting itself) and a collective fiction created by the characters themselves—a post-mortem dream (or work of art) where each life becomes a memory that resurfaces bit by bit, revealing to the protagonists what they were, in a (always emotional) deconstruction of the fiction and a reminder of what the viewers themselves “lived through” for six seasons.